A Monitoring System Using Wireless Sensor Network - Al-Mukhtar, Mumtaz M Ali; Hadi, Teeb Hussein (Al-Nahrain Journal of Science, 2018)
The fast growing in wireless communications and electronics have helped to develop wireless sensor networks. To understand and be able to implement wireless sensor networks several concepts are necessary such as network topology, communication network, communication protocols, and routing that are needed in any monitoring system. In this paper, the performance of WSN based on various topologies scenarios has been investigated. Some techniques useful for managing wireless sensor networks are communication protocols and routing. AODV (Ad-hoc On Demand Distance Vector Routing) routing algorithm is adopted in this work. Cluster-tree, mesh and star topologies are considered in two cases. The first case compares these three ZigBee topologies. The second case compares two scenarios for each ZigBee topologies where all devices in first scenario are fixed and all devices in second scenario are mobile. These cases are simulated by taking into account the specific features and recommendations of the IEEE 802.15.4/ZigBee standard by using OPNET Modeler 14.5.